Research on the Operation Strategy of Rural Logistics Network with Comprehensive Consideration of Cost, Efficiency and Benefit - Panqian DAI; Chenglin LU; Jing XU (Promet (Zagreb))
The high-cost and low-efficiency rural logistics network is a bottleneck that restricts the flow of commodities and economic development between urban and rural areas. In view of this, this paper uses the system dynamics modelling method to first analyse the constituent elements of the rural logistics network operation system and the relationship between them and draw the causal diagram. Secondly, quantify the causal diagram with the dynamics equations, and establish the stock and flow diagram. Thirdly, set the relevant parameters, and carry out the structural, parametric and sensitivity tests with Vensim software. Finally, for the scenarios of dealing with general commodities and fresh agricultural products, the simulation of rural logistics network operation is carried out, which reveals the feedback mechanism between network operation efficiency, logistics cost and operating enterprise benefits, and simulates the implementation effects of different operation strategies from both endogenous and exogenous levels to explore how to build a rural logistics network with high efficiency, low cost and increased benefits. The results show that networked, organised and intelligent operation plans, logistics land use policies, and carbon tax policies are high-leverage measures to reduce cost and increase efficiency in rural logistics networks. However, attention should be paid to distinguishing between implementation stages and the attributes of the implemented enterprises, focusing on the reduction of logistics land cost at the early stage of network construction, levying logistics carbon tax and paying attention to the reduction of the transport fee rate at the mature stage of network operation and increasing policy preferences for fresh agricultural products logistics enterprises.